2004
DOI: 10.4141/p03-083
|View full text |Cite
|
Sign up to set email alerts
|

Response of processing carrot to metribuzin on mineral soils in Nova Scotia

Abstract: . 2004. Response of processing carrot to metribuzin on mineral soils in Nova Scotia. Can. J. Plant Sci. 84: 669-676. Metribuzin was examined as an alternative to linuron and prometryn when prometryn-treated processed carrot in Atlantic Canada in the 1990s could not be exported to the United States, where prometryn was not registered for this crop. Field studies demonstrated that 280 g ha -1 metribuzin applied after the three-leaf crop stage resulted in only minor injury and no yield loss for both a metribuzin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 10 publications
2
18
0
1
Order By: Relevance
“…Studies have shown that tolerance to metribuzin may vary with genotypes cultivated and with edaphoclimatic conditions (Bellinder et al, 1997;Jensen et al, 2004). Possibly, cultivar Nantes is tolerant to the tested doses of the herbicide.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies have shown that tolerance to metribuzin may vary with genotypes cultivated and with edaphoclimatic conditions (Bellinder et al, 1997;Jensen et al, 2004). Possibly, cultivar Nantes is tolerant to the tested doses of the herbicide.…”
Section: Resultsmentioning
confidence: 99%
“…The most widely used method for weed control in large-scale carrot crops has been the application of herbicides (Konieczka et al, 2009;Sasnauskas et al, 2012) and linuron is the main product recommended (Jensen et al, 2004). However, this herbicide has not shown good control of some weed species, which has encouraged producers to seek new alternatives, such as metribuzin, which has a broader range of action.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations